Rapamycin Promotes ROS-Mediated Cell Death via Functional Inhibition of xCT Expression in Melanoma Under γ-Irradiation - Woo, Yunseo; Lee, Hyo-Ji; Kim, Jeongyeon; Kang, Seung Goo; Moon, Sungjin; Han, Jeong A.; Jung, Young Mee; Jung, Yu-Jin (Frontiers in Oncology, 2021)
Although many cancer patients are administered radiotherapy for their treatment, the interaction between tumor cells and macrophages in the tumor microenvironment attenuates the curative effects of radiotherapy. The enhanced activation of mTOR signaling in the tumors promotes tumor radioresistance. In this study, the effects of rapamycin on the interaction between tumor cells and macrophages were investigated. Rapamycin and 3BDO were used to regulate the mTOR pathway. In vitro, tumor cells cocultured with macrophages in the presence of each drug under normoxic or hypoxic conditions were irradiated with γ–rays. In vivo, mice were irradiated with γ–radiation after injection with DMSO, rapamycin and 3BDO into tumoral regions. Rapamycin reduced the secretion of IL-4 in tumor cells as well as YM1 in macrophages. Mouse recombinant YM1 decreased the enhanced level of ROS and the colocalized proportion of both xCT and EEA1 in irradiated tumor cells. Human recombinant YKL39 also induced results similar to those of YM1. Moreover, the colocalized proportion of both xCT and LC3 in tumor tissues was elevated by the injection of rapamycin into tumoral regions. Overall, the suppression of mTOR signaling in the tumor microenvironment might be useful for the improvement of tumor radioresistance.